Conodont and graptolite biostratigraphy of the lower–middle Darriwilian (Middle Ordovician), Cerro Viejo of Huaco, Argentine Precordillera - Mango, Matías Javier (2018)
The distribution of conodonts and graptolites from the upper 13 m of the San Juan Formation and the first metre of the lower member of the Los Azules Formation, Los Gatos and Amarilla creeks, Cerro Viejo of Huaco, Central Precordillera from San Juan, Argentina, is studied. The conodonts from the top stratum of the San Juan Formation at the Los Gatos creek section correspond to the Lenodus variabilis Zone, whereas at the Amarilla creek section, they represent the Yangtzeplacognathus crassus Zone, verifying the diachronous top surface of the San Juan Formation. In the lower member of the Los Azules Formation, 81 conodont elements are recorded from bedding plane surfaces, where the presence of Paroistodus horridus horridus (Barnes & Poplawski) allows to recognize the Y. crassus Zone. On the basis of the graptolite and conodont association, we estimate that the top of the San Juan Formation at Los Gatos creek corresponds to the Levisograptus dentatus Zone, L. dentatus Subzone, whereas at the Amarilla creek, the Arienigraptus angulatus Subzone of the same zone is represented. The presence of the graptolite A. angulatus (Mu) in the lower member of the Los Azules Formation in both sections indicates the L. dentatus Zone (A. angulatus Subzone). The records of graptolites in limestones of the San Juan Formation and of abundant conodonts on bedding plane surfaces of the lower member of the Los Azules Formation are important, taking into account the type of facies where they occur. The conodont records in the referred type of preservation are scarce in the Ordovician, which allows for a more precise biostratigraphic correlation between conodont and graptolite biostratigraphy.